A Microservice Based Architecture to Support Offloading in Mobile Cloud Computing - Cândido, Adriano L.; Trinta, Fernando A. M.; Rocha, Lincoln S.; Rego, Paulo A. L.; Mendonça, Nabor C.; Garcia, Vinicius C. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2019)
Mobile devices are increasingly present in people's daily lives. However, despite the substantial improvement of new generations of smartphones, the amount of information and the complexity of the procedures delegated to these devices still imposes certain restrictions on processing, especially regarding energy consumption. A promise solution to this issue is the technique known as offloading. Over the last few years, several offloading support platforms have been proposed. This work has a particular interest in one of those platforms, called CAOS. Despite its success to perform offloading tasks, CAOS still has problems such as low scalability. In this paper, we report on the refactoring of CAOS into a new microservice-based architecture. Performance and scalability evaluations were performed in both monolithic and microservices versions to show the benefits achieved with the new CAOS architecture.